(untitled) (Bangladesh Journal of Agricultural Research, 2014)
Genetic divergences of 50 wheat lines were studied through Mohalanobiss D2 and principal component analysis for fourteen characters. Genotypes were grouped into four different clusters. Cluster II comprised maximum number of genotypes (twenty one) followed by cluster IV. The inter-cluster distance was maximum between clusters I and III (12.29) indicating wide genetic diversity between these two clusters followed by the distance between cluster I and cluster II (8.28), and cluster III and cluster IV (7.97). The minimum inter-cluster distance was observed between cluster II and cluster IV (4.193) followed by cluster I and cluster IV (4.339) and cluster II and cluster III(4.390) indicating that the genotypes of these clusters were genetically close. The intra cluster distance of all the four clusters was more or less low which indicated that the genotypes within the same cluster were closely related. The highest inter genotypic distance (0.9166) was observed between the genotypes G 40 and G 41and lowest (0.0993) between the genotypes G 22 and G 43. Among the characters, heading days, maturity days, plant height (cm), canopy temperature at vegetative stage, canopy temperature at grain filling stage, grain filling rate (g d-1m-2), 1000- grain weight (g), and grains spike-1 contributed most for divergence in the studied genotypes. Cluster I had the highest mean for grain yield (4711.2 kg/ha), grain filling rate (17.5 g d-1m-2), chlorophyll content at anthesis, and plant height (93 cm). Crosses between I & III, I & II, and III & IV have greater chances to generate more heterotic F1s. Considering magnitude of genetic distance, contribution of different traits toward the total divergence, magnitude of cluster means for different traits and performance the genotypes G10, G 11, G12, G35, G40, G48 of cluster I, G7 of cluster II, G41, G5,and G3 of cluster III and G46, G21 of cluster IV may be considered as good parents for future hybridization program to produce high yielding genotypes. DOI: http://dx.doi.org/10.3329/bjar.v39i2.20414 Bangladesh J. Agril. Res. 39(2): 189-196, June 2014